2021
DOI: 10.3389/fmicb.2021.803309
|View full text |Cite
|
Sign up to set email alerts
|

Dioctanoyl Ultrashort Tetrabasic β-Peptides Sensitize Multidrug-Resistant Gram-Negative Bacteria to Novobiocin and Rifampicin

Abstract: Recently reported peptidomimetics with increased resistance to trypsin were shown to sensitize priority multidrug-resistant (MDR) Gram-negative bacteria to novobiocin and rifampicin. To further optimize proteolytic stability, β-amino acid-containing derivatives of these compounds were prepared, resulting in three dioctanoyl ultrashort tetrabasic β-peptides (dUSTBβPs). The nonhemolytic dUSTBβP 3, comprised of three β3-homoarginine residues and two fatty acyl tails eight carbons long, enhanced the antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…These compounds can be cheaply produced in large amounts and with three diverse leads in clinical trials it is expected that these types of small synthetic mimics will play an important role in the future management of microbial infections. Recent studies on synergistic effects in combination with traditional antibiotics, further highlight the imminent role these compounds may have (103,106,178,179). Collectively, it is shown that a high antimicrobial activity can be obtained using diverse low molecular weight compounds and it is clear that shape matters more than size for optimal activity.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds can be cheaply produced in large amounts and with three diverse leads in clinical trials it is expected that these types of small synthetic mimics will play an important role in the future management of microbial infections. Recent studies on synergistic effects in combination with traditional antibiotics, further highlight the imminent role these compounds may have (103,106,178,179). Collectively, it is shown that a high antimicrobial activity can be obtained using diverse low molecular weight compounds and it is clear that shape matters more than size for optimal activity.…”
Section: Discussionmentioning
confidence: 99%
“…All UTBLPs were prepared by Fmoc SPPS [ 27 ] and as previously described [ 15 , 33 ]. The N-terminus of the amino acids was protected with Fmoc.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro antibacterial activity of the UTBLPs was assessed against wild-type and clinically isolated bacterial strains. To obtain the MIC of the compounds, the microbroth dilution susceptibility assay was performed according to the Clinical and Laboratory Standards Institute (CLSI, Wayne, PA, USA) guidelines [ 36 ] and as previously described [ 15 , 33 ]. Briefly, the compounds at varying concentrations were incubated with bacterial inoculum (5 × 10 5 CFU/mL final concentration) at 37 °C for 18 h. Growth in the form of turbidity was confirmed using an EMax Plus microplate reader (Molecular Devices, San Jose, CA, USA) at 590 nm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations